Efektivitas Sistem Kearsipan Elektronik Human Resource Information System (HRIS) - Claudia Trivena; Yunita Budi Rahayu Silintowe (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
With the development of information technology can create an electronic filing system that is useful for storing documents in the form of soft files. Realizing the effectiveness of the electronic filing system, several aspects need to be considered, namely speed, convenience, efficiency and, safety. In this study, we want to see how effective the electronic filing system is applied to PT Konimex Solo especially in the Human Resource Department. The researcher used qualitative descriptive research. The informants in this study were the Head of Recruitment Administration Section, Recruitment Administration Staff, HRD Administration Staff, and Personnel Section Staff. The results of the study indicate that the Human Resource Department of PT Konimex Solo has been effective in using the electronic filing system "HRIS: Human Resource Information System". Keywords: filing, electronic filing system, effectiveness